2021
DOI: 10.1139/cgj-2019-0548
|View full text |Cite
|
Sign up to set email alerts
|

A finite element approach for determining the full load–displacement relationship of axially loaded shallow screw anchors, incorporating installation effects

Abstract: Screw anchors have been recognised as an innovative solution to support offshore jacket structures and floating systems, due to their low noise installation and potential enhanced uplift capacity. Results published in the literature have shown that for both fixed and floating applications, the tension capacity is critical for design but may be poorly predicted by current empirical design approaches. These methods also do not capture the load-displacement behaviour, which is critical for quantifying performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 47 publications
3
8
0
Order By: Relevance
“…Both load components increase with increasing uplift displacement, but the relative load sharing between the helix and the core decreases and increases respectively. A similar trend was observed for two other simulations (Cerfontaine et al, 2020), but not presented here) that were also validated against centrifuge data (an anchor at lower H/Dh in dense sand and medium-dense sand respectively), although the magnitudes of load carried by the helix (and core) were different at failure (75% of the total capacity was sustained by the helix in medium-dense sand).…”
Section: Soil Structure Interactionsupporting
confidence: 89%
See 3 more Smart Citations
“…Both load components increase with increasing uplift displacement, but the relative load sharing between the helix and the core decreases and increases respectively. A similar trend was observed for two other simulations (Cerfontaine et al, 2020), but not presented here) that were also validated against centrifuge data (an anchor at lower H/Dh in dense sand and medium-dense sand respectively), although the magnitudes of load carried by the helix (and core) were different at failure (75% of the total capacity was sustained by the helix in medium-dense sand).…”
Section: Soil Structure Interactionsupporting
confidence: 89%
“…To ensure the force equilibrium of the soil wedge, the shear stress distribution along the failure mechanism (τsoil) must be balanced by the internal normal distribution acting on the helix (σ'N) and shear stress distribution along the core (τc). A 2-step approximate numerical procedure (using the Finite Element software PLAXIS (2017)) has been previously established and validated against centrifuge tests to simulate the loaddisplacement relationships of screw anchors (Cerfontaine et al, 2020) under monotonic uplift loading, accounting for the effects of installation on the stress field within the soil. The behaviour of a particular anchor (helix diameter 1.7m, core diameter 0.88m, relative embedment ratio 7.4) embedded in dense sand (Relative Density, Dr = 84%) and described in detail in (Cerfontaine et al, 2020;Davidson et al, 2019) is given below as an example.…”
Section: Soil Structure Interactionmentioning
confidence: 99%
See 2 more Smart Citations
“…This work also showed that the failure plane that the shallow mechanism followed was defined by the dilation angle of the sand as found in other applications such as the uplifting of pipelines. It also suggested how existing analytical techniques could be improved to include the findings from FE analysis to give better predictions of screw pile uplift capacity (Cerfontaine et al, 2020).…”
Section: Axial Capacitymentioning
confidence: 99%